ZnO/CuO/M (M = Ag, Au) hierarchical nanostructure by successive photoreduction process for solar hydrogen generation - Kwon, Jinhyeong; Cho, Hyunmin; Jung, Jinwook; Lee, Habeom; Hong, Sukjoon; Yeo, Junyeob; Han, Seungyong; Ko, Seung Hwan (Nanomaterials, 2018)
To date, solar energy generation devices have been widely studied to meet a clean and sustainable energy source. Among them, water splitting photoelectrochemical cell is regarded as a promising energy generation way for splitting water molecules and generating hydrogen by sunlight. While many nanostructured metal oxides are considered as a candidate, most of them have an improper bandgap structure lowering energy transition efficiency. Herein, we introduce a novel wet-based, successive photoreduction process that can improve charge transfer efficiency by surface plasmon effect for a solar-driven water splitting device. The proposed process enables to fabricate ZnO/CuO/Ag or ZnO/CuO/Au hierarchical nanostructure, having an enhanced electrical, optical, photoelectrochemical property. The fabricated hierarchical nanostructures are demonstrated as a photocathode in the photoelectrochemical cell and characterized by using various analytic tools.
Keywords: Hierarchical nanostructure; Photochemical; Photoelectrochemical (PEC) cell; Solar water splitting; Surface plasmon